Kmetijska politika - Turk, Jernej (University of Maribor Press, 2021)
Agricultural Policy. Clear underpinnings of the main theoretical concepts that underlie the scientific character of agricultural policy are presented in this book. A comprehensive understanding of the abundance of theoretical aspects of agricultural economics is complemented with the critical dimension of agricultural policy, which both alleviates us to grasp the basic principles of the latter entirely. Political connotation of farm policy making process is significantly under the scrutiny here. The main objectives, measures and mechanisms of the Common Agricultural Policy (CAP) of EU are elaborated, where the »ever-changing« element of CAP is recognised. Future agricultural policy developmental trends are envisaged in the last part of this monograph. Three strategical aims of modern farm policy are embraced: economically viable production of healthy and safe food, sustainable management of natural resources and balanced territorial development. Review. ’’ With this scientific monograph, we got a fundamental work in Slovenia, which comprehensively deals with agricultural policy. An excellent monograph, where its introductory part presents completely original starting points within the interpretation of the theory of agricultural policy, and as such fills a significant gap in the relevant domestic and international literature in the field of agricultural policy. Political factors play an important role in its formation, so the author says: ’Democracy cannot exist without a pluralism of ideas and a civil democratic society cannot be imagined without respect for the diversity of opinions and values in all their dimensions and colors.’ I highly recommend the book. " Prof. dr. Štefan Bojnec, Faculty of Management, University of Primorska; recipient of the Zois Award for Important Scientific Research Achievements in Economics.